The Fagogoru Ethnopedagogy Textbook Development: A Local Learning Resource for Elementary Schools in Central Halmahera - Abdullah, Oktosiyanti MT.; Bundu, Patta; Saman, Abdul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study focuses on the research and development of local content textbooks using Fagogoru ethnopedagogy. The development process includes needs analysis, model validity testing, practicality testing, and effectiveness testing. Conducted at State Elementary School (SDN) 2 Weda in Central Halmahera Regency, the experimental research involved fourth-grade students. The Fagogoru ethnopedagogy textbook underwent thorough testing for needs analysis, validity, practicality, and effectiveness. Findings from the needs analysis stage, including literature and field studies, indicated a necessity for the Fagogoru ethnopedagogy textbook as a local content learning resource in Central Halmahera Regency. The trial phase demonstrated the textbook's validity, effectiveness, and practicality, deeming it suitable for elementary school use. Both content and construct validity tests met criteria, affirming its value as an educational research product. Practicality and effectiveness tests assessed implementation, student activities, obstacles, and learning outcomes. Practicality testing yielded values within the predetermined standard interval. Effectiveness testing, through hypothesis evaluation, revealed improved learning outcomes using Fagogoru ethnopedagogy. Student response tests indicated positive engagement with the learning activities. The effectiveness assessment of the textbooks confirmed their high efficacy in teaching local content through Fagogoru ethnopedagogy.